An Inclusive Design Criteria: Traditional Market Design for Social Equality - Lugasbaskoro, Norbertus Ruben; Hayati, Arina; Dinapradipta, Asri (The Center for Disability Studies and Services Brawijaya University, 2023)
Nowadays, the traditional market‘s existence is decreasing. Traditional markets are decreasing because of the old-school either design or system. Those, traditional market should adapt over time, beside that interaction becomes a foundation for daily activities and market activities. This interaction links with the social value, which link to equality understandings. Equality's definition relates to activities and interactions in the traditional market.. Indonesian traditional market, in Solo, be an example of diversity in social interaction. Diversity in social interaction links to the architectural approach. Inclusive design in architecture is a form that effectively approaches diversity in social interaction. A Bottom-up method in architecture programming is an appropriate approach that can be used to specify every step used in architecture that can be linked with social equality with interactions as the focus. This article analyzes inclusive design principles and precedents, then can be used as a reference to design somewhere that can be functioned inclusively.